2015
DOI: 10.14202/vetworld.2015.1038-1044
|View full text |Cite
|
Sign up to set email alerts
|

Experimental infection of Aphanomyces invadans and susceptibility in seven species of tropical fish

Abstract: Aim:Epizootic ulcerative syndrome (EUS) causes by aquatic oomycete fungus, Aphanomyces invadans is a dangerous fish disease of a wide range of fresh and brackish water, wild and farmed fish throughout the world. The objective of the present study was to determine the susceptibility of a number of tropical fish species to the EUS and compare the severity of infection between experimental groups.Materials and Methods:Snakehead, Channa striata (Bloch, 1793); snakeskin gourami, Trichopodus pectoralis (Regan, 1910)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…A study shows that Climbing perch was found to be moderately susceptible to the Epizootic ulcerative syndrome (EUS) infection causes by aquatic oomycete fungus (Aphanomyces invadans), compared to EUS susceptible such as Snakehead (Channa striata), tropical snakeskin gourami (Trichopodus pectoralis), koi carb (Cyprinus carpio), and broadhead catfish (Clarias macrocaphalus) [28]. Behavioural changes could be the first response of an organism to environmental change.…”
Section: Resultsmentioning
confidence: 99%
“…A study shows that Climbing perch was found to be moderately susceptible to the Epizootic ulcerative syndrome (EUS) infection causes by aquatic oomycete fungus (Aphanomyces invadans), compared to EUS susceptible such as Snakehead (Channa striata), tropical snakeskin gourami (Trichopodus pectoralis), koi carb (Cyprinus carpio), and broadhead catfish (Clarias macrocaphalus) [28]. Behavioural changes could be the first response of an organism to environmental change.…”
Section: Resultsmentioning
confidence: 99%
“…In their work, live zoospores of EUS were injected to show the histopathological responses of tilapia, however, no visible inflammatory response was found. Afzali et al (2015) stated that in Nile tilapia, fully mature granulomata of varying sizes fused with multinucleated giant cells and formed large granuloma, surrounded with dense fibrous layers and melanin pigments that filled the whole affected area in very early stages of infection. Thompson et al (1999) suggested that giant cell formation did not seem to be an indicator of resistance to EUS while the actual impact of this type of response in respect to fungal infection is still unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Thompson et al (1999) suggested that giant cell formation did not seem to be an indicator of resistance to EUS while the actual impact of this type of response in respect to fungal infection is still unclear. According to Afzali et al (2015), mycotic granulomatous reaction could prevent and halt A. invadans growth only in resistant fish such as Nile tilapia, however in susceptible fish, for example snakehead, gouramies, koi carp, catfish, goldfish, and climbing perch, the rate of hyphal growth was more rapid than granulomatous reaction. Granulomatous reaction could not be an indicator of susceptibility or resistance to the EUS as it varied to the cellular responses of different fish species.…”
Section: Discussionmentioning
confidence: 99%
“…Infection with Aphanomyces invadans, also known as epizootic ulcerative syndrome (EUS), is an OIE-listed disease. It has historically caused mass mortality in cultured and wild fish in Asia and Oceania and recently in North America and Africa (Afzali et al, 2015;Majeed et al, 2017;Iberahim et al, 2018; The World Organisation for Animal Health, 2017).…”
Section: Fungal Diseasesmentioning
confidence: 99%